2019
DOI: 10.1021/acs.jafc.9b05079
|View full text |Cite
|
Sign up to set email alerts
|

The Multifunctional Benefits of Naturally Occurring Delphinidin and Its Glycosides

Abstract: Delphinidin (Del) and its glycosides are water-soluble pigments, belonging to a subgroup of flavonoids. They are health-promoting candidates for pharmaceutical and nutraceutical uses, as indicated by exhibiting antioxidation, anti-inflammation, antimicroorganism, antidiabetes, antiobesity, cardiovascular protection, neuroprotection, and anticancer properties. Glycosylation modification of Del is associated with increased stability and reduced biological activity. Del and its glycosides can be the alternative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 182 publications
0
28
0
Order By: Relevance
“…These forms can also offer an extra advantage of controlling the release of the substance. More studies must decide the appropriate consumption and the most effective type as antidiabetic [ 99 , 102 , 103 , 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…These forms can also offer an extra advantage of controlling the release of the substance. More studies must decide the appropriate consumption and the most effective type as antidiabetic [ 99 , 102 , 103 , 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the physiological activities of quercetin include anticancer, hypoglycemic, and antiobesity activities [42,43,48]. Delphinidin has a variety of pharmacological activities, including anticancer, cardiovascular protection, neuroprotection, antidiabetes, and antiobesity activities [49]. Ferulic acid could offer beneficial effects, such as anticancer, antidiabetes, and antineurodegenerative effects [50].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of psoriasis with synthetic medicines is restricted because of its practicability, comfort, and extreme unfavorable adverse effects like hepatotoxicity and renal damage. 5), Madecassoside (6), Astilbin (7), Biacalin (8), Berberine (9), Boswellic acid (10), Caffeine (11), Camptothecin (12) & Iso-Camptothecin (13), Cannabinoids (14,15,16,17), Chamazulene (18), Chlorogenic acid (19), Cholchicine (20), Curcumin (21), Delphinidine (22), Embelin (23), Fumeric acid (24), Genistein (25), Glycerhiznic acid (26), Gossypol (27), Hypericin (28), Hyperforin (29), Indirubin (30), Isoliquiritigenin (31), Koumine (32), Luteolin (33), P-anisaldehyde (34), Pcoumaric acid (35), P-resinol (36), Podophyllotoxin (37), Polyandric acid A (38), Polyandric acid B (39), Psoralen (40), Quercitin (41), Resveratrol (42), , Syllimarin (43), 4-methylthiobutylisothiocyanate (44).…”
Section: Discussionmentioning
confidence: 99%